Evidence for a modifier of onset age in Huntington disease linked to the HD gene in 4p16 - Djoussé, Luc (2004)
Huntington disease (HD) is a neurodegenerative disorder caused by the abnormal expansion of CAG repeats in the HD gene on chromosome 4p16.3. A recent genome scan for genetic modifiers of age at onset of motor symptoms (AO) in HD suggests that one modifier may reside in the region close to the HD gene itself. We used data from 535 HD participants of the New England Huntington cohort and the HD MAPS cohort to assess whether AO was influenced by any of the three markers in the 4p16 region: MSX1 (Drosophila homeo box homologue 1, formerly known as homeo box 7, HOX7), Δ2642 (within the HD coding sequence), and BJ56 (D4S127). Suggestive evidence for an association was seen between MSX1 alleles and AO, after adjustment for normal CAG repeat, expanded repeat, and their product term (model P value 0.079). Of the variance of AO that was not accounted for by HD and normal CAG repeats, 0.8% could be attributed to the MSX1 genotype. Individuals with MSX1 genotype 3/3 tended to have younger AO. No association was found between Δ2642 (P=0.44) and BJ56 (P=0.73) and AO. This study supports previous studies suggesting that there may be a significant genetic modifier for AO in HD in the 4p16 region. Furthermore, the modifier may be present on both HD and normal chromosomes bearing the 3 allele of the MSX1 marker.